Durability Properties and Leaching Behavior of Fired Clay Brick Incorporated with Gypsum Waste - Mohamad Hilmi, Farah Najwa; Abdul Kadir, Aeslina (Recent Trends in Civil Engineering and Built Environment, 2021)
The chemical industry produced a large amount of gypsum, which was categorized as scheduled waste (SW205). Due to the high content of heavy metals, which poses a threat to the environment, it will give a huge impact. The utilization of gypsum waste in fired clay brick is a method for the elimination of waste that should be disposed of in landfill sites. Brick was manufactured by incorporating 5%, 10%, 15%, 20%, 25% and 30% of gypsum waste and fired at 1050oC using 1oC per minute heating rate. This study focused on durability properties that included wetting drying cycle and compressive strength tests were conducted, while the Toxicity Leaching Behavior Procedure (TCLP) was performed for environmental impact. The results showed that the addition of gypsum waste to bricks would decrease the compressive strength. 10% of gypsum waste is the optimum amount of waste that can be used to be incorporated into fired clay bricks. The leachability test highlight that Al and Fe element the highest among others element. However, most of heavy metals are complied with the United States Environmental Protection Agency (USEPA) and Environmental Protection Agency Victoria (EPAV) standard. Based on this study gypsum brick can be a alternative that provides advantages in terms durability properties and environmentally friendly disposal method.